Influence of hook type on catch of commercial and bycatch species in an Atlantic tuna fishery. (March 2016) - Huang, Hsiang-Wen; Swimmer, Yonat; Bigelow, Keith; Gutierrez, Alexis; Foster, Daniel G.
Abstract: Experimental sets were conducted on a Taiwanese deep set longline fishing vessel operating in the tropical Atlantic Ocean to evaluate the effects of relatively wide circle hooks vs. Japanese tuna hooks with respect to catch rates of both target and incidental species. On circle hooks there were significantly higher catch rates of bigeye tuna ( Thunnus obesus ), yellowfin tuna ( T. albacares ), swordfish ( Xiphias gladius ) and blue sharks ( Prionace glauca ) as compared to tuna hooks. Significantly higher rates of albacore ( T. alalunga ) and longbill spearfish ( Tetrapterus pfluegeri ) were caught on Japanese tuna hooks as compared to circle hooks. Overall, 55 sea turtles were incidentally captured, most ( n =47) of which were leatherback turtles ( Dermochelys coriacea), and capture rates were similar between hook type. Immediate survival rates (percentage alive) when landed were statistically similar for all major target fish species and sea turtles independent of hook type. Most (64%) sea turtles were hooked on the first and second branchlines closest to the float, which are the shallowest hooks deployed on a longline. Lengths of six retained species were compared between hook types. Of these, swordfish was the only species to show a significant difference in length by hook type, which were significantly larger on circle hooks compared to tuna hooks. Additional incentives to use circle hooks would be the increased catch rate in targeted bigeye tuna over traditional Japanese tuna hooks. This international collaboration was initiated in direct response to regional fisheries management organization recommendations that encourage member countries to conduct experiments aimed to identify means to reduce bycatch in longline fishing gear. Information presented may be useful for managers in developing international fisheries policies that aim to balance increases in commercial fishery revenue and endangered species protection. Highlights: Catch risk for tunas, swordfish and blue sharks higher on wide circle hooks. Catch risk for albacore and longbill spearfish higher on Japenese tuna hooks. Hook shape not found to influence rates of immediate survival in fish or sea turtles. A response to RFMOs to identify means to reduce bycatch in longline fisheries.